A poloidal high-k scattering system for NSTX-U. (1st January 2022) - Domier, C.W.; Dannenberg, J.; Zhu, Y.; Liu, X.; Sirigiri, J.R.; Ren, Y.; Stratton, B.; Luhmann, N.C.
Abstract: A previous 5-channel tangential high- k scattering system is being replaced by an 8-channel, poloidal high- k scattering system on the National Spherical Torus eXperiment Upgrade (NSTX-U) device located in Princeton, NJ, USA. The 693 GHz poloidal scattering system replaces a 280 GHz tangential scattering system to study high- k electron density fluctuations on NSTX-U, thereby considerably enhancing planned turbulence physics studies by providing a measurement of the k θ -spectrum of both electron temperature gradient (ETG) and ion temperature gradient (ITG) modes. Two approaches to generating the 693 GHz probe beam are under development: an optically-pumped far-infrared (FIR) laser that generates ∼50 mW, and a compact gyrotron that can potentially generate in excess of 5 W. Large aperture optics collect radiation scattered from density fluctuations in the plasma core at 8 simultaneous scattering angles ranging from 2 to 15° corresponding to poloidal wavenumbers that extend to >40 cm −1 . Steerable launch optics coupled with receiver optics mounted on a 5-axis receiver carriage allow the scattering volume to be placed radially from r / a = 0.3 out to the pedestal region ( r / a ∼ 0.99) and translated horizontally as needed to satisfy wavenumber matching.